2016
DOI: 10.1099/mic.0.000235
|View full text |Cite
|
Sign up to set email alerts
|

GntR family regulator SCO6256 is involved in antibiotic production and conditionally regulates the transcription of myo-inositol catabolic genes in Streptomyces coelicolor A3(2)

Abstract: SCO6256 belongs to the GntR family and shows 74 % identity with SCO6974, which is the repressor of myo-inositol catabolism in Streptomyces coelicolor A3(2). Disruption of SCO6256 significantly enhanced the transcription of myo-inositol catabolic genes in R2YE medium. The purified recombinant SCO6256 directly bound to the upstream regions of SCO2727, SCO6978 and SCO6985, as well as its encoding gene. Footprinting assays demonstrated that SCO6256 bound to the same sites in the myo-inositol catabolic gene cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…S3a), indicating that ROS played an important role in improving the expression of ACT genes. As pathway-specific regulators are generally considered to have a most direct effect on antibiotic production via transcriptional activation of the relevant biosynthetic genes, the pathway-specific regulatory protein was revealed to be ActII-ORF4 in the biosynthesis of ACT 34,35 . Factors that influence the production of ACT are mostly affected by regulation of transcription or translation of actII-ORF4 (SCO5085) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…S3a), indicating that ROS played an important role in improving the expression of ACT genes. As pathway-specific regulators are generally considered to have a most direct effect on antibiotic production via transcriptional activation of the relevant biosynthetic genes, the pathway-specific regulatory protein was revealed to be ActII-ORF4 in the biosynthesis of ACT 34,35 . Factors that influence the production of ACT are mostly affected by regulation of transcription or translation of actII-ORF4 (SCO5085) 36 .…”
Section: Resultsmentioning
confidence: 99%
“…S. coelicolor A3(2) genome contains 56 genes for GntR-like proteins representing five subfamilies. Eleven of them were described experimentally (Hoskisson et al, 2006; Rigali et al, 2008; Horbal et al, 2013; Persson et al, 2013; Cen et al, 2016; Yu et al, 2015, 2016; Tsypik et al, 2016, 2017), but the low molecular ligands have been identified in only two cases. Glucosamine 6-phosphate is the effector molecule bound by a master regulator DasR which links nutrient stress to antibiotic production (Rigali et al, 2008).…”
Section: Introductionmentioning
confidence: 99%